EKSISTENSI DAN PERANAN PENYULUH AGAMA ISLAM MEDAN JOHOR DALAM MENGURANGI KECEMASAN PADA MASA PANDEMI COVID-19 - Haidir Haidir; Muhammad Hizbullah; M. Guffar Harahap (Jurnal Al-Fatih, 2021)
Actually, this research was conducted with the aim of looking at the existence and at the same time the role of the Islamic Religious Counselor (PAI) Kec. Medan Johor in reducing anxiety for the Muslim community of Medan Johor, Medan City in the face of the Covid-19 pandemic. This research was conducted in the area of KUA Kec. Medan Johor by using social situations, namely all 10 Islamic religious instructors in Medan Johor and the community using purposive sampling and snowball sampling techniques. The research method used is a survey and naturalistic method with qualitative descriptive data processing. This research was conducted for 6 months. While the data sources of this study were obtained based on observations, interviews, and documentation. Based on the research results, it can be found that: 1) That PAI Kec. The 10 Medan Johors are at the forefront of providing guidance and counseling for the community in increasing faith and worship practices in daily life. And also in terms of development, namely the development of people's mental attitudes so that they can always live according to Islamic teachings, 2) PAI as a profession and spearhead of government in conveying religious messages in government language. PAI in carrying out the task of guidance and counseling in the district. Medan Johor based on a decree from the Head of the Regional Office of the Ministry of Religion of North Sumatra Province and the technical guidance from the Ministry of Religion's Guidance for Medan City, 3) PAI Kec. During the Covid-19 pandemic, Medan Johor was active in providing guidance and counseling both face-to-face and through the media to private fostered groups in their respective kelurahan and jointly assisted groups, namely PWBI Kwala Bekala. PAI directly conducts guidance and counseling face to face once a month with the theme "Muslims in the Corona period" which is divided into several subtitles. Meanwhile, you can indirectly upload materials, both written and video, on social media such as YouTube channels, whatshap groups, Instagram, and Facebook.